Establishment of National Laboratory Standards in Public and Private Hospital Laboratories - Soghra Anjarani; Nooshafarin Safadel; Parisa Dahim; Rana Amini; Saeed Mahdavi; Siamak Mirab Samiee (Tehran University of Medical Sciences, 2013)
In September 2007 national standard manual was finalized and officially announced as the minimal quality requirements for all medical laboratories in the country. Apart from auditing laboratories, Reference Health Laboratory has performed benchmarking auditing of medical laboratory network (surveys) in provinces. 12th benchmarks performed in Tehran and Alborz provinces, Iran in 2010 in three stages. We tried to compare different processes, their quality and accordance with national standard measures between public and private hospital laboratories. The assessment tool was a standardized checklist consists of 164 questions. Analyzing process show although in most cases implementing the standard requirements are more prominent in private laboratories, there is still a long way to complete fulfillment of requirements, and it takes a lot of effort. Differences between laboratories in public and private sectors especially in laboratory personnel and management process are significant. Probably lack of motivation, plays a key role in obtaining less desirable results in laboratories in public sectors.